Stability and Change of Cool and Hot Executive Functions Across Middle Childhood and Early Adolescence: A Person-Oriented Longitudinal Perspective. - Brandt, Ariadne; Gericke, Christian; Bondü, Rebecca; Elsner, Birgit (Developmental Psychology, 2025)
With the aim of unraveling the developmental dynamics of executive functions (EF), this person-oriented longitudinal study investigated the stability and change of EF across 3 years from middle childhood into early adolescence. A community sample of 1,657 school children (52% female) completed behavioral tasks measuring three cool (inhibition, working memory updating, cognitive flexibility) and two hot EF facets (affective decision making [DM], delay of gratification) at three timepoints. Via random-intercept latent transition analyses, children were assigned to one of four profiles of EF performance at T1 (M = 8.36, SD = 0.95) and T2 (M = 9.11, SD = 0.93): all-average, low-delay, regulated-DM, and low-inhibition. At T3 (M = 11.06, SD = 0.92), the regulated-DM and low-inhibition profiles disbanded, and new high-hot EF and mixed-hot EF profiles emerged. Across 3 years, 35% of children remained assigned to their initial profile, whereas 22% of children experienced profile transitions reflecting increasing EF performance (e.g., all-average to high-hot EF), and 21% experienced decreasing performance (e.g., all-average to low-delay). Profile membership was differentially associated with age and binary sex. These results suggest substantial interindividual differences and intraindividual change across EF performance—particularly at the onset of adolescence and for hot facets. The findings offer new explanations for contradictory results from variable-oriented research on hot EF development. Furthermore, by disaggregating unique longitudinal EF transitions, differentiated patterns of stability and change were revealed. The findings provide a basis for future research and applications targeting individual EF strengths and weaknesses during development. Public Significance Statement: This study identified four subgroups of children aged 6–11 years that differed in their expression of three cool and two hot executive functions. Furthermore, this study identified various subgroup transitions (i.e., stable, increasing, and decreasing performance) 1 and 3 years later, indicating inter- and intraindividual differences, including both stability and change, in executive function development. These findings advocate for more research using person- rather than variable-oriented perspectives in order to uncover coexisting patterns and associations of executive functions that may otherwise go undetected.